METODE-METODE PEMBELAJARAN - Mardiah Astuti; Farel Zahardi; Agnes Tiara; Airin Mey Lestari; Anisa Rahma Utami; Daffa Aulia Padaya; Muhammad Riyadh (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
In the teaching and learning process, appropriate methods are needed for the learning process to take place and achieve learning objectives. Learning methods are one component of a learning strategy. To improve student understanding, learning methods are needed. With effective learning methods, students will easily understand and comprehend everything conveyed by the teacher during the classroom learning process. A good teaching and learning process should use a variety of teaching methods, alternating between one learning method and another. The teacher's task is to select appropriate methods to create a teaching and learning process that fosters student interest in learning. In the teaching and learning process, appropriate methods are needed for the learning process to take place and achieve learning objectives. Learning methods are one component of a leaming strategy. To improve student understanding. learning methods are needed. With effective learning methods, students will easily understand and comprehend everything the teacher conveys during the classroom learning process. A good teaching and learning process should utilize a variety of teaching methods, alternating between one learning method and another. The teacher's task is to select appropriate methods to create a teaching and learning process that fosters student interest in learning.